2022
DOI: 10.1111/jbi.14542
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of future range shifts in lichens and mosses under climate change

Abstract: Aim: Lichens and mosses play important functional roles in all terrestrial ecosystems, particularly in tundra and drylands. As with all taxa, to maintain their current niche in a changing climate, lichens and mosses will have to migrate. However, there are no published estimates of future habitat suitability or necessary rates of migration for members of these groups at the global scale.Taxon: Lichens and mosses. Location: Global.Methods: Using global occurrence data, we conducted ensemble distribution models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 100 publications
1
5
0
Order By: Relevance
“…Annual Mean Temperature, contributing 11.72% to the microbiome variation, regulates resource availability, primary productivity (Pierre et al, 2020), and microbial interactions (Apple et al, 2006; Knapp & Huang, 2022). The influence of these variables on lichen physiology, growth, and metabolism, including their effects on metabolic rates, water availability, and nutrient dynamics, aligns with already existing research (Finger-Higgens et al, 2022; Ladrón de Guevara et al, 2018; Mallen-Cooper et al, 2023; Nascimbene et al, 2016). Notably, while temperature-related variables emerge as key contributors, precipitation-related variables, such as precipitation seasonality and annual precipitation, play a comparatively minor role.…”
Section: Discussionsupporting
confidence: 78%
“…Annual Mean Temperature, contributing 11.72% to the microbiome variation, regulates resource availability, primary productivity (Pierre et al, 2020), and microbial interactions (Apple et al, 2006; Knapp & Huang, 2022). The influence of these variables on lichen physiology, growth, and metabolism, including their effects on metabolic rates, water availability, and nutrient dynamics, aligns with already existing research (Finger-Higgens et al, 2022; Ladrón de Guevara et al, 2018; Mallen-Cooper et al, 2023; Nascimbene et al, 2016). Notably, while temperature-related variables emerge as key contributors, precipitation-related variables, such as precipitation seasonality and annual precipitation, play a comparatively minor role.…”
Section: Discussionsupporting
confidence: 78%
“…High temperatures are likely to limit biocrust taxa at their arid range edge by enhancing evaporation, thereby restricting the ability of biocrust organisms to fix carbon. In addition, two global studies have shown that temperature is often the dominant control of the ranges of biocrust communities and species (Mallen‐Cooper et al, 2023; Rodriguez‐Caballero et al, 2018). We also derived six variables related to moisture availability: (1) annual rainfall, (2) summer rainfall, (3) non‐summer rainfall, calculated as the total rainfall from March to November, (4) the number of days where rainfall exceeded 1 mm, (5) the mean number of consecutive days between rainfall events >1 mm and (6) the number of days with >1 mm rainfall and maximum temperature > 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…These studies indicate that biocrusts usually fail to colonise soils that have become compacted or unstable, because they cannot anchor to the surface and are easily buried by sediment (Weber et al, 2016). If dispersal and establishment limitations can be overcome, many generalist biocrust species have the potential to expand in total area at the global scale (Mallen‐Cooper et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The GCMs used in this study were the Canadian Earth System Model version 5 (CanESM5) (Swart et al, 2019), the Institut Pierre-Simon Laplace Climate Model version 6A Low Resolution (IPSL-CM6A-LR) (Boucher et al, 2020), and the Model for Interdisciplinary Research on Climate version 6 (MIROC6) (Tatebe et al, 2019). The selected GCMs have been widely used in SDMs to make predictions of species' occurrence and impact of climate change (e.g., Adenkanmbi et al, 2023;Chen et al, 2023;Mallen-Cooper et al, 2023). The GCMs were selected by maximizing the intermodel distance among them according to Sanderson et al (2015).…”
Section: Forecastingmentioning
confidence: 99%